Money handling and obesity: a test of the exaptation hypothesis - Karve, Shraddha; Shurpali, Ketaki; Dahanukar, Neelesh; Paranjape, Sharayu; Jog, Maithili; Belsare, Prajakta; Watve, Milind (Current Science, 2011)
The food reward centres in the brain play a central role in the regulation of food intake and thereby obesity. In the modern lifestyle, a number of artificial rewards such as money have been introduced and brain areas evolved for handling food rewards appear to be exapted to handle money and other rewards. This implies that the changing behaviour related to these rewards could influence obesity. Considering money as a reward, we conducted a survey of 211 full-time cashiers to test whether ownership over cash, amount of cash handled and duration of cash-handling work correlated with obesity parameters. Body mass index was significantly affected by sex, ownership, amount of money handled and duration of cash-handling service. Waist-to-hip ratio was significantly affected by sex, amount of money handled and marginally by ownership. The results are compatible with the exaptation hypothesis. It is possible that increasing importance of non-food rewards may play a significant role in the obesity epidemic.
Keywords: Body weight; economics of obesity; exaptation hypothesis; money handling

Phyllocladane diterpenes from anisomeles heyneana - Kulkarni, Roshan R.; Shurpali, Ketaki; Gawade, Rupesh L.; Sarkar, Dhiman; Puranik, Vedavati G.; Joshi, Swati P. (Journal of Asian Natural Products Research, 2012)
New phyllocladane diterpene, phyllocladan-16 alpha,17-dihydroxy-19-oic acid (1), together with known phyllocladane diterpene, phyllocladan-16 alpha,19-diol (2), cembrane diterpene ovatodiolide (3), sitosteryl-3-O-beta-D-glucoside (4), and verbascoside (5), were isolated from aerial parts of Anisomeles heyneana. The structure of compound 1 was elucidated by 1D and 2D NMR analyses which included HSQC, HMBC, and nuclear overhauser effect spectroscopy (NOESY) experiments as well as X-ray crystallography. This is the first report of phyllocladane diterpenes from genus Anisomeles. Compounds 1, 3, 4, and 5 were evaluated for inhibition of Mycobacterium tuberculosis and 3 was found to exhibit anti-mycobacterial activity with IC90 6.53 mu g/ml. Compounds 1, 3, and 5, at 100 mu g/ml, were also evaluated for inhibition of Thp-1 cell lines, and compounds 1 and 3 showed 59.02% and 96.4% inhibitions, respectively.
Keywords: Anisomeles heyneana; Lamiaceae; Mycobacterium tuberculosis; phyllocladane diterpenes

Antimycobacterial labdane diterpenes from leucas stelligera - Kulkarni, Roshan R.; Shurpali, Ketaki; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Journal of Natural Products, 2013)
Phytochemical investigation of the acetone extract of the aerial parts of Leucas stelligera afforded four new compounds (1-4) belonging to the labdane diterpene series as well as two known flavones, velutin (5) and chrysoeriol (6). Structure elucidation of the new compounds was carried out using ID and 2D NMR spectroscopic data and single-crystal X-ray crystallography of compound 1. Compounds 1-4 exhibited selective antimycobacterial activity against Mycobacterium tuberculosis with IC50 values in the range 5.02-9.80 mu g/mL.

New pimarane diterpenes and other antimycobacterial metabolites from anisochilus verticillatus - Kulkarni, Roshan R.; Shurpali, Ketaki; Khedkar, Vijay M.; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2016)
Phytochemical investigation of the acetone extract of the aerial parts of Anisochilus verticillatus afforded a new 8,9-secopimarane diterpene (1), two new isopimarane diterpenes (2, 3) and the known ursolic acid (4), beta-amyrin (5), -amyrin (6), stigmast-5-en-3-one (7) and hydroxychavicol (8). Structures of the new compounds were elucidated with the help of 1D and 2D nuclear magnetic resonance spectroscopic data, and single crystal X-ray crystallography of compound 3. Compounds 2 and 8 inhibited Mycobacterium tuberculosis H37Ra with an IC50 of 11.3 (IC90 of 20.0g/mL) and 12.5g/mL, respectively. Correspondingly, molecular docking studies with Extra Precision Glide revealed a correlation between score and biological activity for these compounds to describe the molecular basis for the most significant SAR results.
Keywords: alanine racemase; Anisochilus verticillatus; antimycobacterial activity; diterpenes; Lamiaceae